Characterisation of mitotic phosphorylation on chromokinesin KIF4A - Ang, Anthony Wei Tzerl (2015)
Chromokinesins are a group of kinesins characterized by their association to the arms of chromosomes during mitosis. Given their unique localization during mitosis, chromokinesins are thought to be responsible for the polar ejection force during chromosome congression. Polar ejection force is the anti-poleward force that pushes the chromosome arms toward the spindle equator, and acts in an opposing manner to the poleward force. The poleward force is evident during metaphase to anaphase transition where segregated chromosomes move towards the poles. One member of chromokinesins in human is KIF4A. In addition to the arms of mitotic chromosomes, KIF4A is observed on the mitotic spindle, spindle midzone and spindle midbody. Studies on KIF4A has found that the KIF4A does seem to contribute to chromosome congression, as its absence has been known to cause increased failure rate of chromosome congression. On top of that, KIF4A has been found to interact with proteins that are involved in processes such as chromosome condensation, DNA repair, gene expression and cytokinesis. In spite of such information, the exact role of KIF4A is still uncertain. Moreover, no regulation of KIF4A has been elucidated. I thus seek to identify possible regulations of KIF4A during mitosis, with the aim of uncovering the functions of KIF4A. In particular, I am interested in phosphorylation as a mechanism of regulation for KIF4A. I found that KIF4A is indeed phosphorylated by several kinases during mitosis, and these phosphorylations could regulate the functions of KIF4A.